The royal palaces of Spain - Hernández Ferrero, Juan A.; Rivas, Humberto (New York [u.a.] : Abbeville Press, 1998)
Het paleis van Madrid - El Pardo - El Escorial - Aranjuez - La Granja de San Ildefonso; Riofiro - Reales Alcázar de Sevilla - La Almudaina (Palma de Mallorca)
Keywords: Palaces -- Spain; Spain -- Kings and rulers -- Dwellings